Cementing a polyethylene cup into a well fixed acetabular metal-on-metal resurfacing component?: an experimental investigation - Klotz, Matthias C. M.; Jäger, Sebastian; Kretzer, Jan Philippe; Beckmann, Nicholas A.; Thomsen, Marc N.; Bitsch, Rudi G. (HIP international, 2017)
IntroductionAdverse reactions to metal debris often indicate revision surgery in metal-on-metal (MoM) hip arthroplasty and an exchange of the MoM bearing into either a metal on polyethylene or a ceramic-on-polyethylene articulation. At the moment the removal of the entire implant system is the most reasonable method. In order to avoid bone loss caused by the removal of a well-fixed acetabular component, the purpose of this study was to measure the stability of a cemented polyethylene (PE) cup in an acetabular hip resurfacing component and to examine if such a method could be suitable for clinical use.MethodsPE cups were cemented into 2 different hip resurfacing components and biomechanical tests were applied to measure failure torques under lever out and rotational load.ResultsIn all cases failure of the interface between the resurfacing components and the cement layer occurred at a very low load (0.14 Nm-61.50 Nm).DiscussionThe early failure occurred due to lacking interdigitation of cement and the polished metal surface. Thus we warn against cementing a PE cup into acetabular hip resurfacing components for clinical use.
Gesehen am 25.09.2018